Islam intensified: snapshot historiography and the making of Muslim identities. Issue 2 (3rd April 2019) - Ragab, Ahmed
ABSTRACT: The celebrated, and oft-criticised, 1001 Inventions exhibition offered a particular vision of Islam and Muslims in the West that is imbedded in the postcolonial reality of the post-9/11 world. Built around the coupling of Islam and science, the exhibition and its critics negotiate the place of Muslims in the contemporary world as mapped through the simultaneous intensification of Islam and science as epistemological categories. Such intensification is built on a symmetrical epistemology that deploys science as a universal value perceivable in snapshot historiographies. The article here argues that the exhibition and connected narratives, seen as examples of producing Muslim identities in the West, use the juncture of Islam and science, written in conforming agency, to re-inscribe and affirm the definition of Islam as a core and unchanging identity for Muslims.